IMPLEMENTATION OF HEALTH SCHOOL PROGRAM (UKS) IN ELEMENTARY SCHOOL - Yeny Kusumawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Background:The Health school program (UKS) is an effort to develop healthy life habits with three main programs which include: health education, health services, and fostering a healthy lifestyle in school.This researchdescribesthe implementation of the health school program and determine factors influencing the UKS's implementation.Method: Qualitative research design and descriptive. Informantsdeterminedto use purposive sampling.Subjects research washeadmaster, homeroom teachers (I, III, VI), sports teacher, and UKS teacher.Techniquedata collection wasan observation, interviews, and documentation. Validity data was checked with the triangulation technique. Qualitative data analysis used an interactive model based on the theory of George C. Edward III, which consists of communication, resources, dispositions, and bureaucratic structures.Result: The health school programhaven’t been implemented optimally, especially in the resource. Facilityfor UKS isn’t complete and the number is insufficiency. There isn’ta specific budget for the implementation ofthe health school program. Supporting factor is communication; there is threehealth school programthat always communicated to school residents. Disposition factor; there is a good understanding of health school program implementers. Bureaucratic structure factor; there is SOP's existence in implementing the health school program.Conclusion:Implementation of health school program has not been maximized, so it needs to be supported by all factors, both communication factors, resource factors, disposition factors, and bureaucratic factors.